Agroecological transitions in value chains – A multiple case analysis - Charry, Andres; Vargas, Alejandra; Narjes, Manuel; Gonzalez, Carolina (2024)
Agroecology is increasingly recognized as a promising approach to address the challenges confronting our food systems. While evidence underscores its potential impacts, there is a critical knowledge gap regarding the successful scaling of agroecological practices, particularly in the global south. The CGIAR Initiative on Agroecology (AE-I), aims at understanding the mechanisms conducive to the adoption and expansion of agroecological principles across diverse landscapes, including market- type interventions such as value chain (VC) and business models (BM) development.